INTERAKSI ADAT DAN ISLAM DALAM BANGUNAN MASJID KUNO DI TANAH DATAR - Syahrul Rahmat (Berkala Arkeologi Sangkhakala, 2019)
As one of the traditional buildings in Minangkabau, the mosque built before the 20th century is unique in term of the building shape. Customary leaders have a major role in the mosque construction, especially in Tanah Datar District, West Sumatra. The customary embodiment as community's culture also influences the meaning of every part of the mosque building. This indicates that at a certain time, customs and Islam had a quite intense interaction to leave a mark on the building architecture. The research conducted using a historical research method. This research aimed to discover the interaction of custom and religion in term of mosque building built in the early of 18th and 20th century. The interaction between custom and Islam are analyzed in form of physical, meaning, and idea.